Exploring EFL Students’ Efforts in Speaking Skill - Indra Syahputra; Sofyan A. Gani; Nurul Inayah (Universitas Syiah Kuala, 2017)
The purpose of this study was to describe the efforts that students made in developing speaking skill. Descriptive qualitative was used in this study; the subjects were 65 students at year 2015 studying at English Education department, Syiah Kuala University, Banda Aceh. The instrument used in this study was questionnaire. The questionnaire questions were adapted from the activity scale from Pace Kuh. The questionnaire revealed that speaking experience such as communicating by using English with friends and family was the highest effort chosen by the students because it was very comfortable to perform speaking among the closest people. Club and organization was the lowest effort chosen by the student. The students took part in organization just to spend their spare time. The students thought that joining in an organization did not have contribution in developing their speaking skill. The implication of this study was to motivate the students to make some efforts to develop their speaking skill. Focusing in certain effort will help the students improve their speaking skill mastery. In addition, for the suggestion, the students should create activities that promote English communication in order to develop their speaking skill.